Blue Carbon Coastal Sequestration for Climate Change Mitigation - Alongi, Daniel M. (SpringerBriefs in Climate Studies,, 2018)
This work summarizes the science and management of a rapidly expanding topic in climate science, namely adaptation and mitigation. The term 'blue carbon' refers to the rates, pathways and volumes of greenhouse carbon sequestered in coastal estuarine and marine ecosystems such as salt marshes, mangroves and seagrass meadows. Blue carbon and its vital role in climate change mitigation are central to this book. Readers find summaries and analysis of both the basic scientific data and data from blue carbon field projects, and a practical guide on how to manage a successful blue carbon field project. There is a discussion on how to maximize the carbon sequestration and consideration of whether blue carbon projects make a difference. The work is not only of interest to scholars involved in climate science, but also those in the marine sciences, and those in ecosystem ecology, biogeochemistry; geochemistry; estuarine and marine plant ecology.